3D Assessment in Posttraumatic Ankle Osteoarthritis. (February 2021) - Kvarda, Peter; Heisler, Lukas; Krähenbühl, Nicola; Steiner, Caspar Samuel; Ruiz, Roxa; Susdorf, Roman; Sripanich, Yantarat; Barg, Alexej; Hintermann, Beat
Background: Auto-generated 3-dimensional (3D) measurements based on weightbearing cone-beam computed tomography (CT) scan technology may allow for a more accurate hind- and midfoot assessment. The current study evaluated the reliability and clinical relevance of such measurements in patients with posttraumatic end-stage ankle osteoarthritis. Methods: Seventy-two patients treated at our institution for posttraumatic end-stage ankle osteoarthritis, with available weightbearing conventional radiographs and a cone-beam CT scan, were analyzed. Twenty healthy individuals aged between 40 and 70 years served as controls. Seven variables were measured on weightbearing conventional radiographs (2D) and compared to 3D measurements that were based on reconstructions from weightbearing cone-beam CT scans. The reliability of each measurement was calculated and subgroups formed according to commonly observed deformities. Results: Inter- and intraobserver reliability was superior for 3D compared to 2D measurements. The accuracy of 3D measurements performed on osteoarthritic ankles was similar to 3D measurements performed on healthy individuals. Thirty-three of the 72 included patients (46%) evidenced an inframalleolar compensation of a supramalleolar/intra-articular ankle deformity (78% = varus compensation; 22% = valgus compensation), whereas 24 of those 72 patients (33%) showed no compensation or a further increase of a supramalleolar/intra-articular ankle deformity (67% = varus deformity; 33% = valgus deformity). Conclusion: Auto-generated 3D measurements of the hind- and midfoot were found to be reliable in both healthy individuals and patients with posttraumatic end-stage ankle osteoarthritis. Such measurements may be crucial for a detailed understanding of the location and extent of hindfoot deformities, possibly impacting decision making in the treatment of end-stage ankle osteoarthritis. Level of Evidence: Level III, comparative study.